The Quest - Smith, Wilbur A. (New York Thomas Dunne Books, an Imprint of St. Martin's Press, 2007)
When ancient Egypt is threatened by a series of terrifying plagues, including the failure of the Nile River, the pharaoh sends the warlock Taita on a perilous quest to the source of the Nile to uncover the cause of the catastrophe.
English Fiction.
Keywords: Egypt -- Warlocks -- Paranormal fiction -- Taita (Fictitious character : Smith) -- Nile River